2022
DOI: 10.3390/plants11172278
|View full text |Cite
|
Sign up to set email alerts
|

Anthracnose Disease Control and Postharvest Quality of Hass Avocado Stored in Biobased PLA/PBAT/Pine Essential Oil/Chitosan Active Packaging Nets

Abstract: For sale in the domestic market, Hass avocados are kept in non-biodegradable plastic nets and stored at an ambient temperature. The fungus Colletotrichum gloeosporioides can cause important losses at this stage. Consequently, formulations based on polylactic acid (PLA)/poly (butylene adipate-co-terephthalate) (PBAT) 60/40 biodegradable blends added with pine essential oil (PEO) at 10, 12, 14, and 20% and coated with 1% chitosan (CH) were used for the elaboration of nets, which were evaluated on C. gloeosporioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The methodology for fiber elaboration was proposed by Black-Solis et al [12] and Correa-Pacheco et al [13]. The fibers were extruded from a mixture of two biodegradable polymers: PLA (IngeoTM Biopolymer 7001D, NatureWorks, LLC, Blair, NE, USA) and PBAT (Ecoflex ® F Blend C1200, BASF, Mexico City, Mexico) in a 60/40 ratio (PLA/PBAT), and cactus stem flour at 3% using canola oil (Valley Foods ® , Michoacán, Mexico) at 4% as a plasticizer.…”
Section: Fiber Elaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…The methodology for fiber elaboration was proposed by Black-Solis et al [12] and Correa-Pacheco et al [13]. The fibers were extruded from a mixture of two biodegradable polymers: PLA (IngeoTM Biopolymer 7001D, NatureWorks, LLC, Blair, NE, USA) and PBAT (Ecoflex ® F Blend C1200, BASF, Mexico City, Mexico) in a 60/40 ratio (PLA/PBAT), and cactus stem flour at 3% using canola oil (Valley Foods ® , Michoacán, Mexico) at 4% as a plasticizer.…”
Section: Fiber Elaborationmentioning
confidence: 99%
“…Their results showed that the antioxidant capacity was notably higher in tomatoes grown under greenhouse conditions, while the quality was maintained during storage. In addition, Correa-Pacheco et al [13] packed avocado 'Hass' fruit in similar polymeric matrix nets, but added chitosan and pine essential oils. They reported no side effects on the quality of the avocado at the end of the storage period and markedly less infection caused by the fungus Colletotrichum gloeosporioides.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al used AgNPs loaded nanocrystal cellulose (NCC-Ag) to mixed with PLA/PBAT to prepare green antibacterial nanocomposites (Ma et al, 2016). Correa-Pacheco et al obtained biobased PLA/PBAT/pine essential oil/chitosan active packaging nets (Correa-Pacheco et al, 2022). Biodegradable polybutylene adipate (PBAT) containing copper oxide nanoparticles (CuONPs) was used as raw material to prepare bioactive packaging bioactive film by adding different concentrations of enzymic nanocellulose fibers (ENC).…”
Section: Introductionmentioning
confidence: 99%